1987
DOI: 10.1063/1.339699
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of tin-doped indium-oxide film in hydrogen and argon plasma

Abstract: The degradation of tin-doped indium-oxide (ITO) films in glow-discharge plasmas of hydrogen and argon have been investigated. Parameters which have been varied for the study include the temperature of ITO under ion bombardment, the rf power density, the time of exposure to plasma, and the gas flow rate. After bombardment, scanning electron micrograph observation, measurement of sheet resistance, transmittance and reflectance, and Auger analysis have been carried out to decide the extent of degradation. Magnetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 7 publications
1
35
0
Order By: Relevance
“…For example, Banerijee et al reported the visible transmission and infrared reflection (at 2100 nm) of magnetron-sputtered ITO films could reach ~90% and ~75%, respectively [72]. In addition, high visible transmittance (>80%) and infrared reflection (~70% at 2500 nm) are observed in ITO thin films prepared by Aerosol Assisted CVD (AACVD) [74].…”
Section: Tin-doped Indium Oxide (Ito)mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Banerijee et al reported the visible transmission and infrared reflection (at 2100 nm) of magnetron-sputtered ITO films could reach ~90% and ~75%, respectively [72]. In addition, high visible transmittance (>80%) and infrared reflection (~70% at 2500 nm) are observed in ITO thin films prepared by Aerosol Assisted CVD (AACVD) [74].…”
Section: Tin-doped Indium Oxide (Ito)mentioning
confidence: 99%
“…High quality ITO coatings have been grown by several deposition techniques including magnetron sputtering [72,73], chemical vapour deposition (CVD) [74], sol-gel [75], spray pyrolysis [76], and pulsed laser deposition (PLD) [77] on a glass substrate. For example, Banerijee et al reported the visible transmission and infrared reflection (at 2100 nm) of magnetron-sputtered ITO films could reach ~90% and ~75%, respectively [72].…”
Section: Tin-doped Indium Oxide (Ito)mentioning
confidence: 99%
“…Being highly resistive to hydrogen environment, ZnO was proven to be a valid alternative, on laboratory scale, to fluorine doped tin oxide, which is typically used as a TCO in the large scale production of silicon thin film solar cells [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…According to Banerjee et al, ITO films degraded under hydrogen plasma showed large reduction in transmittance, increase in sheet resistance, substantial changes in surface morphology due to the formation of In rich hillocks, and large nonuniformity of surface composition due to segregation and coalescence of In rich clusters [9]. Therefore, the understanding and estimation of degradation behavior of ITO films is essential to overcoming the deterioration in performance and improving the lifetime and quality of electronic devices.…”
Section: Introductionmentioning
confidence: 98%